2010
DOI: 10.1007/s00412-010-0279-4
|View full text |Cite
|
Sign up to set email alerts
|

Replication dynamics at common fragile site FRA6E

Abstract: The replication dynamics at common fragile site FRA6E has been evaluated by molecular combing and interphase fluorescent in situ hybridisation (FISH) in primary human lymphocytes cultured under normal or aphidicolin-induced stress conditions. FRA6E is one of the most frequently expressed common fragile sites of the human genome. It harbours several genes, PARK2 being regarded as the most relevant one. According to the results obtained from interphase FISH analysis, FRA6E can be considered a mid-late-replicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 51 publications
3
64
1
1
Order By: Relevance
“…Delayed replication has been considered to be a key molecular feature associated with aCFS expression (Arlt et al 2006;Palumbo et al 2010). However, we found G-negative banding to be the dominant predictor of fragility in our aCFS vs. NFR model, and initial studies examining G vs. R banding patterns and S-phase replication timing showed that G-negative bands are replicated early in S phase (Holmquist et al 1982).…”
Section: Replication Timingmentioning
confidence: 99%
“…Delayed replication has been considered to be a key molecular feature associated with aCFS expression (Arlt et al 2006;Palumbo et al 2010). However, we found G-negative banding to be the dominant predictor of fragility in our aCFS vs. NFR model, and initial studies examining G vs. R banding patterns and S-phase replication timing showed that G-negative bands are replicated early in S phase (Holmquist et al 1982).…”
Section: Replication Timingmentioning
confidence: 99%
“…The PARK2 gene is located within a known chromosomal fragile site (FRA6E) and consequently, rearrangements of PARK2 are expected to be frequent in cancer cells (19)(20)(21). Furthermore, Clark and colleagues mate-paired sequenced the genome of the U87MG cell line and found an intrachromosomal translocation within the PARK2 gene (22).…”
Section: Parkin-expressing Glioma Cells Exhibit Delayed Entry Into MImentioning
confidence: 99%
“…By molecular cytogenetics (Fig. 3A-3C), we excluded the presence of large genomic rearrangements, deletions, or duplications in R311K-p63 OMESCs [15,16]. The resolution of the analysis on DNA extended fibers (molecular combing; Fig.…”
Section: Resultsmentioning
confidence: 99%